IMPLEMENTASI MOTIF GEDOG DALAM DESAIN RANSEL PRIA SEBAGAI SARANA PENGENALAN BUDAYA TUBAN - Pramana, Achmad Bhakti Nusa; Nurhidayat, Martiyadi; Bahri, Nurul Fitriana (eProceedings of Art & Design, 2024)
Tuban is a district in East Java which is located on the coast, with its strategic location making Tuban one of the international trade centers so that many cultures influence people's daily lives. One of Tuban's unique cultural heritage is Gedog batik. Gedog Batik is unique, especially in terms of the fabric making process. By woven traditionally using non-machine looms (ATBM). The distinctive "dok dok dok" sound produced when this tool operates was the inspiration for the name "Gedog" on this batik.For all its value, this batik is still little known to the public, so efficient efforts are needed to promote it. One way is through using backpacks as promotional media, considering the popularity of backpacks, especially among men aged 19-25 years. The research was conducted using qualitative methods that focused on collecting and analyzing data from participants. The SCAMPER design method is used to develop innovative ideas in creating men's backpacks that implement the Gedog motif. The result of this research is a men's backpack whose every part is tailored to the target user, with the addition of a Gedog motif design which is expected to be an effective means of introducing Tuban culture to the intended target. Keywords: Batik Gedog, implementation, men’s backpack